Adult classic Bartter syndrome: a case report with 5-year follow-up and literature review - Le Jiang; Dongmei Li; Qiansha Guo; Yunfeng Li; Lei Zan; Rihan Ao (Endocrine Journal)
Bartter syndrome (BS) is a rare, inherited salt-losing renal tubular disorder characterized by secondary hyperaldosteronism, hypokalemia, hypochloremia, metabolic alkalosis, and low-to-normal blood pressure. Classic BS, or BS Type 3, the most common subtype in the Asian population, is caused by a molecular defect in ClC-Kb, a voltage-gated chloride channel in renal tubules, due to CLCNKB gene mutation. Because the onset of BS is more common in children than in adults, the diagnosis, treatment outcomes, genotype/phenotype association, and follow-up of adult-onset BS Type 3 are limited. This case report describes the findings in a 20-year-old man who was admitted with hypokalemic paralysis, with clinical manifestations were similar to those of Gitelman syndrome (GS); however, the patient was later diagnosed to have BS Type 3 through genetic testing (NM_000085.4 (CLCNKB): c.1052G>T). A literature review showed that no homozygous mutations have been reported to date. After 5 years of treatment and follow-up, we found that this genotype requires high levels of potassium and is prone to urinary protein and metabolic syndrome. Distinguishing adult-onset BS from GS is challenging in clinical practice. However, genetic diagnosis can help solve this problem effectively, and genotypes play a guiding role in treatment planning.